Pathological Nipple discharge: a comparison between breast ultrasound and mammography - Alhadethy, Dhuha M; Altameemi, Enam K; Khalaf, Laith A; Kamal, Areege Mustafa (Journal of the Faculty of Medicine Baghdad, 2021)
Background:Nipple discharge is a relatively common complaint of females in reproductive age and after menopause. Objectives: The aim of this stud was to compare the radiological findings of mammography and ultrasound in women with pathological nipple discharge of different pathology. Methods: mammography and ultrasound was done for a total of 50 patients attending the National center of Early detection of Breast cancer with pathological nipple discharge. Ultrasound guided FNA was performed for all cases, and histopathology was available for eleven case. Results: ultrasound was able to provide clue of possible underlying cause for all pathological nipple discharge whereas mammography was negative in 54%. Ultrasound was more sensitive in diagnosing malignant breast lesions associated with pathological nipple discharge (85.7%) but less specific (88.3%) as compared with mammography which had (71.4%) sensitivity and (90.6%) specificity. Negative predictive value of ultrasound was 97.4% , mammography was 95.1% and of non-bloody nipple discharge was 94%. Conclusion: Ultrasound is essential to complete pathological nipple discharge workup, particularly when mammography is normal, to rule out the possibility of neoplastic changes and to provide clues for nonneoplastic etiology that may guide the management.